KEPEMIMPINAN TRANSAKSIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA KARYAWAN - Khilmi Izdiana; Naili Farida; Andi Wijayanto (Universitas Diponegoro, 2014)
Human resource is one resource that has a very important role in a variety of sectors , because human resources is a factor to mobilize other resources . Human resources need special attention in handling from its management to improve employee performance. This study aims to determine whether there is influence between Transactional Leadership (X1), Cultural Organization (X2) on employee performance (Y2) Through the Work Motivation (Y1). The population of this study were 70 employees as respondent. Likert scale was used as measurement scale. Linear regression and path analysis were used in the data analysis with SPSS 20.00. The results of partially data processing shows that each Transactional Leadership, Organizational Culture, and Work Motivation influence the performance of employees in PT. Pura Nusapersada unit PM 8 Kudus. The result of path analysis that work motivation as a mediator